Relationship between blood eosinophils and clinical characteristics in a cross-sectional study of a US population-based COPD cohort. (March 2016) - DiSantostefano, Rachael L.; Hinds, David; Van Le, Hoa; Barnes, Neil C.
Abstract: Background: Current evidence suggests that blood eosinophil levels (Eos) are associated with chronic obstructive pulmonary disease (COPD) treatment response and natural history. This analysis investigated the relationship between Eos levels and clinical characteristics in a representative cohort of US subjects with spirometry-defined COPD. Methods: Cross-sectional data from the National Health And Nutrition Examination Survey (NHANES 2007–2010) of subjects ≥40 years with spirometry-defined COPD and Eos data (n = 948) were analyzed. Differences in clinical characteristics by Eos level (≤2%, >2%) were compared using chi-square tests. Characteristics associated with Eos >2% were identified using multivariate logistic regression modeling. Characteristics associated with Eos >2% among subjects with normal lung function, plus other cut-points among the COPD population, were evaluated post hoc. Findings: Most participants had Eos >2%; 70.7% with spirometry-defined COPD and 65.5% with normal lung function. Older age, male gender, and severe current asthma were significantly associated with Eos >2% in COPD subjects. The Eos ≤2% COPD group had higher reported rates of previous heart attack and anemia. Among participants with normal lung function, Eos >2% was associated with being male, being overweight/obese, older age, hay fever, and congestive heart failure. Interpretation: In this large US-based cohort, Eos >2% was prevalent in participants with COPD and normal lung function. Among participants with COPD, Eos >2% was associated with specific characteristics including lower rates of some co-morbidities; however, the clinical implications and relationships between Eos levels, COPD mechanisms, and risk of outcomes require further evaluation. Highlights: Blood eosinophils (Eos) may be related to COPD phenotypes and treatment response. Most COPD subjects had Eos >2%; Eos were similarly distributed in normal lung function. Older age, being male, and severe asthma were associated with Eos >2% in COPD. Eos >2% in COPD was also associated with a lower risk of some co-morbidities. Clinical significance and mechanism for these relationships require further study.